QASAS AL-QUR`ĀN DALAM SUDUT PANDANG PRINSIP-PRINSIP STRUKTURALISME DAN NARASI (Pengantar Studi Sastra Narasi al-Qur`an) - Moh. Wakhid Hidayat (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
Literary appreciation to the Koran becomes a fundamental idea in this study. Literary appreciation is used, because the Koran is a glorious Arabic literary bible which is strongly believed in its perfection and beauty. The object of this paradigm is not the unwritten words of Allah, but that of Allah that have been recorded in Arabic media, written in musha and communicated by human being. The main goals of this study are analyzing qasas al-Qur’ān from the aspect of principal structuralism and narrative theory. Analyzing qasas al-Qur’ān from this view is in harmony with tartīb al-āyāt theory and unity story theory by surah of Khalafullāh, and Qusb narration of classification. This analysis proposes three classifications of qasas al-Qur’ān and they are different from, for example, Manna’ al-Qassān, Mussafā Sulaimān, Khalafullāh, yet they share something in common with classification of Qasb. These classifications are: the first is one narration in one surah, the second is the collection of short narrations in a sequence of the surah, and the third is the collection of short narration in non-sequence of surah. These classifications become in harmony with the Koranic order, which collects its verses in one surah, in stead of collecting themes from various surah.